STUDENTS’ PERCEPTION AND ATTITUDE TOWARDS ENTREPRENEURSHIP IN HO CHI MINH CITY: A CASE STUDY AT HO CHI MINH CITY CADRE ACADEMY - Vy, Trinh Yen; Anh, Pham Ngoc Van; Anh, Phan Thi Hue (American International Journal of Social Science Research, 2021)
In the context of the 4th industrial revolution, it is becoming increasingly difficult to ignore entrepreneurship. Starting a business is expected to create economic growth, make positive contributions to socio-economic development. It is gradually emerging and becoming a topic of much interest from researchers and businesses. So far, however, there has been little discussion about student entrepreneurship. The present research examines the perception and attitude of Ho Chi Minh City students towards entrepreneurial activity through a case study at Ho Chi Minh City Cadre Academy. Specifically, the study addresses the following questions: 1/attitude towards entrepreneurship 2/ reasons for students to be confident to start a business 3/ reasons for students to be not self-confident to start a business. This study employed questionnaires and in-depth interviews as methods to come to the results of the research. The authors selected a non-probability sampling of 240 students in classes of 5 majors at Ho Chi Minh City Cadre Academy for the questionnaire. The findings of this study suggest that the percentage of students who are not confident in starting a business is higher than that of those who are self-confident. The study also finds out the social factors affecting students’ confidence in starting a business and why they are not confident of entrepreneurship.